Unlocking the Power of Economic Agglomeration: How Digital Finance Enhances Urban Land Use Efficiency Through Innovation Ability and Rationalization of Industrial Structure in China - Zijing Hu; Bowen Li; Guanyu Guo; Yuan Tian; Yue Zhang; Chengming Li (Land, 2024)
With the rapid progression of urbanization, Chinese cities are encountering an increasingly severe shortage of land resources. To examine the role of digital finance (DF) in promoting economic agglomeration (EA) and subsequently improving urban land use efficiency (ULUE), this paper focuses on 274 prefecture-level cities from 2013 to 2020. By employing an interaction effect model, the study analyzes how DF influences the relationship between EA and the enhancement of ULUE. The findings demonstrate that DF positively moderates the effect of EA on enhancing ULUE. The analysis reveals that DF can accelerate resource flows and more effectively promote the enhancement of ULUE by amplifying the positive influence of EA on regional innovation ability (IA) and the rationalization of industrial structures (RIS). Furthermore, the heterogeneity analysis indicates that this moderating effect is particularly pronounced in China’s central and eastern regions, areas with higher rates of internet penetration, and regions with stronger innovation capacities. Based on these findings, this paper proposes policy recommendations such as promoting regional integration and supporting innovation in DF. These insights contribute to the theoretical discourse on EA in the digital era and provide critical and practical guidance for optimizing the development of agglomeration economies and constructing a high-quality development framework.